Efficacy of multi-wave locked system laser therapy on nerve regeneration after crushing in Wister rats - Alayat, Mohamed Salaheldien Mohamed (J Phys Ther Sci, 2021)
[Purpose] To investigate the efficacy of the multi-wave locked system laser therapy on the regeneration of peripheral nerve injuries by evaluating the functional, electrophysiological, and morphological changes of the crushed sciatic nerve in Wistar rats. [Materials and Methods] Sixty male Wistar rats (200–250 g) were randomly assigned to control negative, control positive, or laser groups and subjected to no laser therapy or crushing, to crushing without laser therapy, or crushing followed by multi-wave locked system laser therapy five times/week for four weeks (power=1 W, energy density=10 J/cm(2), total energy=100 J), respectively. Functional, electrophysiological, and morphometric analyses were performed before and 7, 15, 21, and 28 days after crushing. The sciatic functional index, compound motor action potential amplitude, motor nerve conduction velocity, and nerve and myelin sheath diameters were measured. [Results] The sciatic functional index value decreased significantly, while the compound motor action potential amplitude, motor nerve conduction velocity, nerve diameter, and myelin sheath diameter increased significantly in the laser group post-treatment compared to the values in the control groups. [Conclusion] Multi-wave locked system laser therapy was effective in accelerating the regeneration of crushed sciatic nerves in Wistar rats.